Diversity and Abundance of Fish and Invertebrates of Semerak Estuary and Adjacent Inshore Waters, Kelantan. - Chong, V.C.; A.R, Jamizan; Z., Mohamad Yazid; M., Rizman-Idid; S.H., Muhammad Ali; P., Natin (Malaysian Journal of Science, 2010)
Construction of the Tok Bali channel-jetty and channelization of the Semerak River in Bachok had removed and reduced its fringing mangroves, nevertheless, the river modification has improved estuarine circulation. There was invasion of the estuary by at least 59 marine and euryhaline species, including 47 fish species, but prawn and crab fauna were poor. The fish in the estuary included economically-important species of leiognathids, lutjanids, catfishes, barracudas, pomfrets and squids. Bachok’s coast provides habitat, feeding and nursery areas to mainly juveniles of 71 fish and 22 invertebrate species. Leiognathids, mullids, cephalopods and portunid crabs were the dominant coastal fishes and invertebrates. The coastal fish fauna including a few reefassociated species was much richer (59 species) to the north of Tok Bali jetty than south of it (16 species). The Leiognathidae with eight species displayed clear spatial distribution from coastal to estuarine waters.